The FIT FIRST 10 Dose–Response Study: Evaluating Implementation Outcomes (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Aligned with the UN Sustainable Development Goals, promoting physical activity (PA) in schools requires scalable and sustainable strategies. This study evaluated the implementation of FIT FIRST 10 (FF10), a Danish multi-sport programme designed to enhance PA, fitness, and wellbeing among 2nd and 3rd graders. We assessed implementation fidelity, feasibility, and determinants of sustainability, with a focus on how programme dosage influenced real-world delivery.Methods: FF10 was implemented over 20 weeks in a cluster randomised controlled trial involving 27 schools. Schools were randomised to full dose (3 × 40 min/week, n = 9), half dose (1.5 × 40 min/week, n = 9), or control (n = 9). Intervention teachers received a one-day training course, printed manuals, and sports equipment. Fidelity was tracked through weekly teacher logbooks. Implementation outcomes – acceptability, appropriateness, feasibility – and COM-B-based determinants were measured via online questionnaires. Descriptive statistics were used to compare mean scores across groups.Results: Eighteen intervention schools (38 classes) participated: nine schools (18 classes) in the full-dose group and nine schools (20 classes) in the half-dose group. On average, teachers in the full-dose group delivered 2.8 sessions per week (standard deviation (SD) = 0.4), while those in the half-dose group delivered 2.0 sessions (SD = 0.5), indicating high fidelity relative to assigned dose. Teacher scores for implementation outcomes were moderate to high. In the half-dose group, mean scores were: acceptability: 4.0, appropriateness: 3.7, and feasibility: 3.8. In the full-dose group, the corresponding scores were: 3.7, 3.6, 3.7. Social opportunity was rated highly in both groups (>4.0), indicating strong perceived support and norms for delivering the programme. However, motivation was generally lower (